(untitled) (Research, Society and Development, 2023)
Digital citizenship is about the citizenship of the algorithmic, datatified, connected, and sensorized world of metaverses, multiverses, big data, and artificial intelligence. It is the expression of a new type of architecture that promotes the emergence of a computational ecology made of people, data, algorithms, sensors, forests, weather, viruses, and cities. This connection challenges us to a new cognitive policy in the field of Education. The objective of the article is to discuss ways of knowing and producing knowledge related to the development of computational thinking in K-12 Education to understand how this language is promoted and produced in an immersion path in the city, understood as a territory of hybridizations. The experiences in the city are part of research conducted at the International Research Group on Digital Education, GPe-dU UNISINOS/CNPq, developed from inventive, sympoietic, interventionist, and gamified pedagogical practices. As a research method, it appropriates the intervention-research cartographic method for the production and analysis of data. The results presented are based on elements present in the reticular and connective epistemologies, in the theory of inventive cognition, and in the concepts of transorganic connective act, and atopic inhabitancy. The results indicate that computational thinking is being leveraged in the co-articulation between human and non-human entities, from a citizen OnLIFE Education perspective, contributing to its interdisciplinary and transversal understanding, as well as pointing to the emergence of an ecological cognitive policy in education.